Germanium-tin (GeSn) p-channel fin field-effect transistor fabricated on a novel GeSn-on-insulator substrate - Lei, Dian (2020)
Germanium-tin (GeSn) p-channel fin field-effect transistor (p-FinFET) was realized on a novel GeSn-on-insulator (GeSnOI) substrate. The high-quality GeSnOI substrate was formed using direct wafer bonding technique and was layer-transferred from a 300-mm GeSn/Ge/Si donor wafer. Material quality was examined using atomic force microscopy, high-resolution transmission electron microscopy, Raman spectroscopy, and high-resolution X-ray diffraction. The fabricated GeSn p-FinFETs exhibit a small subthreshold swing (S) of 79 mV/decade at V DS of -0.05 V (by a device with L CH of 200 nm and W Fin of 30 nm), good control of short channel effects, and high intrinsic transconductance (G m,int = 702 μS/μm at V DS of -0.5 V for L CH of 80 nm). Low-temperature mobility analysis was performed on the GeSn p-FinFETs. High effective hole mobility (μ eff ) (210 cm 2 /V·s at 290 K and 398 cm 2 /V·s at 5 K) is achieved. The GeSn p-FinFETs presented in this paper exhibit the highest G m,int /S sat at V DS of -0.5 V for all the reported GeSn p-FETs to date.